CREATING AND SHAPING ENTREPRENEURIAL MIND TO FACE THE DIGITAL ERA SOCIETY - Sapto Imambachri; Sugiyarto Sugiyarto; Edi Junaedi (Universiitas Pamulang, 2022)
ABSTRACT Entrepreneurship plays a very vital role in the economic growth of a country, including Indonesia, the role of entrepreneurship in Indonesian economy not only helps the government and society to increase per capita income, but also includes job creation for the people of Indonesia. Seeing the importance of Micro, Small and Medium Enterprises (MSMEs) to support the Indonesian economy going forward, the Government of Indonesia is aggressively continuing to improve Indonesia's infrastructure, as well as economic growth centers, such as the inauguration of the Mandalika Circuit of West Nusa Tenggara (NTB), 18 -20 March which initiated the emergence of many entrepreneurs. Indonesia's entrepreneurship ratio is only around 3.47 percent, and this figure is quite low when compared to fellow ASEAN countries such as Singapore which reached 8.76 percent, Thailand 4.26 percent and Malaysia 4.74 percent.